Positive Framing in Children’s Pandemic Narratives: A Case Study of the Cerita Ceritaku Ceritamu Corona Edition Book - Riama Maslan Sihombing; Ester Anggun Kusumaningtyas (Wacana Seni Journal of Arts Discourse, 2025)
The children’s book Cerita Ceritaku Ceritamu Corona Edition (C3EC) is the first book in Indonesia to narrate the children’s experiences in the early stages of the COVID-19 pandemic. The book was written by 23 Indonesian children from Banda Aceh to Papua, with each story visualised by some of the children’s book illustrators. A difference is evident in perspective between the writers in the textual narrative and the illustrators in the visual narrative. The textual narrative in the story frequently depicted conflicts, with 56% focusing on challenges related to online learning and limited playtime. The majority climax phase of the textual narrative expresses the negative mood, characterised by struggle, sadness, and hopelessness. In contrast, the illustrators predominantly visualised the resolution phase, with 51% of characters portrayed as happy and 8% as sad. This study aims to uncover why illustrators chose favourable conditions during the pandemic and focused on the resolution phase when determining visual narrative scenes. This research used a mixed method. Data were collected through literature review, observation, interviews, and questionnaires. These findings describe the selection of the illustrator’s favourable conditions, the selection of the resolution phase, and the creative process behind the C3EC book story. This study’s impact shows that illustrators felt a responsibility to inspire resilience in readers, thereby transcending the author’s perspectives.